I used to think I could fly [compact disc] - McRae, Tate, 2003- (RCA, 2022)
Following the success of the chart-topping single You Broke Me First, Tate McRae releases her long-awaited debut album. The album features the tracks Chaotic and She's All I Wanna Be.